Infected branchial cleft cyst in a newborn - Jennifer B. Frazer; Dafydd A. Davies; Joanne M. Langley (Elsevier, 2022)
We report a case of a newborn with a Staphylococcus aureus infection of a branchial cleft anomaly (BCA) and review the characteristics and frequency of infection of this congenital anomaly over 18 years at our center. Six percent of patients presented as neonates and 42% of BCAs became infected.